Qualitative perspectives on the sustainability of sexual health continuous quality improvement in clinics serving remote Aboriginal communities in Australia. Issue 5 (5th May 2019) - Gunaratnam, Praveena; Schierhout, Gill; Brands, Jenny; Maher, Lisa; Bailie, Ross; Ward, James; Guy, Rebecca; Rumbold, Alice; Ryder, Nathan; Fairley, Christopher K; Donovan, Basil; Moore, Liz; et al.
Abstract : Objectives: To examine barriers and facilitators to sustaining a sexual health continuous quality improvement (CQI) programme in clinics serving remote Aboriginal communities in Australia. Design: Qualitative study. Setting: Primary health care services serving remote Aboriginal communities in the Northern Territory, Australia. Participants: Seven of the 11 regional sexual health coordinators responsible for supporting the Northern Territory Government Remote Sexual Health Program. Methods: Semi-structured in-depth interviews conducted in person or by telephone; data were analysed using an inductive and deductive thematic approach. Results: Despite uniform availability of CQI tools and activities, sexual health CQI implementation varied across the Northern Territory. Participant narratives identified five factors enhancing the uptake and sustainability of sexual health CQI. At clinic level, these included adaptation of existing CQI tools for use in specific clinic contexts and risk environments (eg, a syphilis outbreak), local ownership of CQI processes and management support for CQI. At a regional level, factors included the positive framing of CQI as a tool to identify and act on areas for improvement, and regional facilitation of clinic level CQI activities. Three barriers were identified, including the significant workload associated with acute and chronic care in Aboriginal primary care services, high staff turnover and lack of Aboriginal staff. Considerations affecting the future sustainability of sexual health CQI included the need to reduce the burden on clinics from multiple CQI programmes, the contribution of regional sexual health coordinators and support structures, and access to and use of high-quality information systems. Conclusions: This study contributes to the growing evidence on how CQI approaches may improve sexual health in remote Australian Aboriginal communities. Enhancing sustainability of sexual health CQI in this context will require ongoing regional facilitation, efforts to build local ownership of CQI processes and management of competing demands on health service staff.